Use of the Archimedes navigation system to diagnose peripheral pulmonary lesions: preliminary Italian results - Lanfranchi, Filippo; Mancino, Laura; Foltran, Gabriele; Nicole’, Lorenzo; Michieletto, Lucio (Frontiers in Oncology, 2024)
Diagnosis of peripheral pulmonary lesions (PPL) is one of the most challenging fields in early lung cancer diagnosis. Despite novel techniques and new approaches to the periphery of the lung, almost 25% of PPL remains undiagnosed. Virtual bronchoscopy navigation (VBN) potentially allows to sample PPL previously not reachable with conventional bronchoscopy. In this preliminary report, we described 9 cases of PPL (in which conventional bronchoscopy did not reach the lesion) sampled with VBN, from which we obtained a diagnosis in 7 out of 9 cases (77.8%), consistent with other reported results in literature. More large-scale data are needed to whether VBN can increase diagnostic yield (DY) of PPL.